TRANSFORMASI TEKS INFOGRAFIS SEBAGAI STRATEGI UNTUK MENGATASI KESULITAN BELAJAR PADA KEMAMPUAN MEMBACA PEMAHAMAN TEKS EKSPOSISI - Hasisah, Siti Nur; Umaya, Nazla Maharani; Riyanawati, Dyah Susy (Balai Bahasa Sumatera Utara, 2023)
This research aims to determine whether the reading comprehension ability of Expository Text in class X TE 4 (Electrical Engineering 1), SMKN 4 Semarang students can improve by utilizing text transformation into infographics. The research subjects were class X TE 4 students with a total of 36 students consisting of (24) male students and (12) female students. The research method used is data collection is using qualitative methods, through interviews with several questions related to the problems faced by students. After qualitative data is obtained, students will be given an infographic of one of the exposition texts and 5 questions related to the exposition text given. The results of the research can be seen through the extent to which students are correct in answering the questions and will be proven through the scores obtained from the 5 questions that have been sent. From the infographic media provided, students were very enthusiastic in observing and answering questions quickly and correctly just by reading the infographic images. In this research, it can be seen that all students are busy looking for answers and no one is lazy anymore. Based on the research results, as many as 90% of their 36 students were able to answer all the questions correctly. So it can be concluded that infographic transformation can increase the reading ability of students in class X TE 4 SMKN 4 Semarang.